Unresolved Issues Regarding the Research and Practice of Cognitive Behavior Therapy: The Case of Guided Discovery Using Socratic Questioning. Issue 1 (April 2014) - Kazantzis, Nikolaos; Fairburn, Christopher G.; Padesky, Christine A.; Reinecke, Mark; Teesson, Maree
<x content-type="archive" xml:space="preserve">Abstract</x> This article presents a panel discussion on the integration of collaborative empiricism, specifically Socratic Questioning, into cognitive behaviour therapy. The panel comprised experts in research and practice who had been invited as keynote presenters for the 34th National Conference for the Australian Association of Cognitive and Behaviour Therapy, held in Sydney, Australia. Experts responded to questions regarding (a) the definition of Socratic dialogue, and (b) whether the purpose of Guided Discovery using Socratic Questioning is to impart information, correct, or dispute patient cognitions. The session was well attended by mental health professionals from around the globe and the panel enjoyed the opportunity to discuss questions and comments from those in attendance. This article presents this exchange so that the broader AACBT membership may benefit from the ideas and comments generated.